P389 Congenital syphilis in a developed country – a case report. (June 2019) - Giva, Sheiniz; Ferguson, Wendy; Egan, Roisin; Kaninde, Abhidhamma; O'Sullivan, Rebecca; O'Gorman, Joanne; Hayes, Breda
Abstract : Background: Congenital syphilis (CS) is an infectious disease caused by the spirochete Treponema pallidum acquired by the foetus in utero. Transmission is transplacental and it may occur at any stage during pregnancy. Clinical Case: A male infant born in Ireland at 37 weeks to an Irish lady of traveller ethnicity who did not seek antenatal care. The infant was unwell at birth requiring ventilatory and inotropic support; he had copious nasal secretions. Birth weight of 2.06 Kg (<2 nd centile) and head circumference of 31 cm (2 nd centile) demonstrated growth restriction. The mother's delivery serology revealed positive T. pallidum ( T.pallidum IgG/IgM positive), T. pallidum particle agglutination assay (TPPA) positive, Rapid Plasma Reagin(RPR) positive (1:128) and T. pallidum IgM positive. The mother had suffered 'flu-like' symptoms during the pregnancy and had pruritus in the palms and soles. Newborn Investigations: Serological testing for T. pallidum was positive (TPPA 1:2480, RPR 1:8). CSF testing was also performed (RPR titre 1;1, TPPA 1:640). Other investigations also revealed thrombocytopenia (35, 000/mm 3 ) and elevated Alkaline Phosphatase (384 U/L) and Aspartate aminotransferase (85 U/L). Abdominal ultrasound confirmed hepatosplenomegaly and cranial ultrasound showed cysts in the caudothalamic grooves bilaterally consistent with congenital infection. Long bones x-ray demonstrated a thick periosteal reaction in the diaphysis and metaphysis of the upper and lower limb bones bilaterally and a 'sawtooth pattern' of metaphyseal abnormality in the right distal radius and ulna which is pathognomonic of CS. Treatment: The infant received IV benzylpenicillin as per guidelines. Regular follow up is scheduled with the Infectious Diseases Team and other relevant services. Discussion: In the 21st century, a worldwide re-emergence of syphilis infection and an increase in early infectious syphilis (EIS) numbers and congenitally infected cases have been reported, notably in developed countries. In 2017, there were 398 notifications of EIS in Ireland (8.4 per 100, 000 population compared to 3.7 per 100, 00 population in 2012) and 25% of females with EIS were pregnant at the time of diagnosis. Although the incidence of EIS in pregnancy is low (0.6/1000 births), early detection and treatment reduces the risk of CS. The consequences of untreated infection, as described in this case can be significant. Conclusion: This case highlights the continuing importance of antenatal screening in a low incidence country to identify EIS in pregnancy. To our knowledge this is the first case of symptomatic CS born to a mother of ethnic Irish origin in 2 decades.